Not All in the Same Boat. Socioeconomic Differences in Marital Stress and Satisfaction During the Covid-19 Pandemic - Turliuc, Maria Nicoleta; Candel, Octav Sorin (Frontiers in Psychology, 2021)
The Covid-19 pandemic is a global threat that affects a large part of the population, but the risks associated with it are higher for some people compared with others. Previous studies show that lower socioeconomic status (SES) is associated with more chronic stress and less marital satisfaction. Thus, the uncertainty caused by the pandemic might greatly affect those who were already vulnerable. This longitudinal study explores the extent to which stress originated outside (external) and inside (internal) the relationship is associated with marital satisfaction during the Covid-19 pandemic and whether the associations are different based on the socioeconomic status of the participants. The study was conducted at 2 points in time (first, immediately after the national lockdown was instituted; second, after the lockdown ended) with a sample of 144 married Romanian couples. We used the Actor-Partner Interdependence Model with Mediation and multi-group SEM analysis. Higher levels of external stress were associated with subsequent lower marital satisfaction for women with higher SES. For the couples with lower SES, men’s level of internal stress during the first assessment mediated the relationship between their higher level of external stress at the first time point and their partner’s lower marital satisfaction during the second assessment. Our results show that men and women respond differently during a crisis and that couples with lower SES are more prone to greater stress and a higher decrease in marital satisfaction. We finally suggest that the therapists, health professionals, policy makers, and researchers should take into account the existing vulnerabilities of a couple when offering psychological and health services during the Covid-19 pandemic.